Understanding Sexual Assault Victimization Among College Men: A Mixed Methods Approach - Downs, Emily M (East Carolina University, 2019)
Introduction: Sexual assault is a major concern on college campuses, but most research has focused on women as victims and men as perpetrators. Despite this, there is evidence that men also experience sexual assault, albeit less frequently than women (Banyard et al., 2007). Unfortunately, there is little research available that focuses on men’s experiences with sexual assault, likely due to multiple factors including the smaller victim pool, low disclosure frequency, rape myths regarding men and sexual assault, and a lack of inclusion of certain assault experiences pertaining to men in sexual assault screening measures (Cantor et al., 2015; Navarro & Clevenger, 2017; Struckman-Johnson & Struckman-Johnson, 1992). Prior studies attempting to assess the prevalence of sexual assault in college men vary greatly in their findings—from 3-28% of men surveyed—largely due to differing sexual assault criteria, methodology, and time frames assessed (Forsman, 2017). Furthermore, to fully understand men’s experiences, there is a need for qualitative research examining men’s descriptions of their assaults. Methods: The current study evaluated the responses of 58 men (11.2%) who experienced a sexual assault who participated in a large online study of sexual assault among college students. Participants completed an assault characteristics measure, which assessed multiple aspects of the assault, as well as screening measures for depression, PTSD, and hazardous alcohol use. They also provided a written description of the sexual assault experience. Results: The majority of men described a female perpetrator, most often an acquaintance or romantic partner. Alcohol and party contexts were frequently described. Significant proportions of men scored above the cutoffs for probable depression, PTSD, and hazardous alcohol use. Thematic analysis of assault narratives supported the existence of several types of assault (e.g., incapacitated, violent assault, mismatched intentions), as well as themes related to the negative impact of the assault, minimization of the assault’s impact, emasculation, as well as rape myths (e.g., it was not rape because the victim had an erection). Discussion: Results supported both similarities and differences in the sexual assault experiences of men and women. For example, there was evidence male rape myths affect how men label their assault experiences. As another example, many men minimized the impact of the assault, and some were able to use their size/strength to stop the assault, or believed that they could have stopped the assault if they chose to do so. Additional work should examine the experiences of male victims and develop tailored interventions for this population.
Keywords: sexual assault; college men; mixed methods; qualitative